(untitled) (Research, Society and Development, 2025)
Introduction: Sepsis is a severe clinical condition resulting from a dysregulated host response to infection, frequently associated with high hospital mortality rates. In Brazil, its occurrence shows important regional and demographic disparities, making it necessary to understand its epidemiological profile. Objective: This study aimed to analyze the mortality profile from sepsis in Brazil and by regions, between 2018 and 2022, considering sociodemographic variables and places of occurrence. Methodology: This is an observational, analytical, and retrospective study using secondary data from the Mortality Information System (SIM/SUS), with a quantitative approach, employing descriptive statistics with absolute and relative frequencies. All deaths recorded as septicemia classified under ICD-10 codes A40 and A41 were included. Mortality rates were calculated per 100,000 inhabitants, standardized using the direct method, with the year 2020 as the reference population. The 95% confidence intervals (CI95%) were also estimated. Results: A total of 113,059 deaths from sepsis were recorded in Brazil during the analyzed period. The Southeast Region showed the highest standardized rates (67.3/100,000 inhabitants), followed by the South and Northeast regions. Older adults aged 80 years and over had the highest rates (1,071.1/100,000 inhabitants). Disparities were also observed by race/skin color, with higher coefficients among white and black individuals. Most deaths occurred in hospital settings. The results highlight the high mortality from sepsis in the country and reveal regional, age-related, and racial inequalities. The importance of qualified surveillance, early intervention, and standardized clinical protocols to reduce preventable deaths is reinforced.